Synthesizing geovalent adjustment model for outward foreign direct investment performance among Malaysian medium sized firms / Azman Mohd Isa - Mohd Isa, Azman (Institute of Graduate Studies, UiTM, 2018)
Outward Foreign Direct Investment (OFDI) activities have mainly been studied for Multi National Corporations (MNCs) but lesser for Small-Medium Enterprises (SMEs). This study shall make use of Geovalent Adjustment model introduced by Stephen Guisinger in 2001 as pedestal in analyzing the multi-faceted concepts of OFDI-related theories and Internationalization theories; in hope for finding similarities between the two. This study shall specifically make use of Malaysian Medium-sized firms as sample object for which they are already matured, both in terms of business operations as well as financial standings. This study hypothesizes that any similarities found from the said two foundational theories, could be synthesized into becoming one model, which would then provide an ease ground for mediumsized firms to adopt and practice. This study examines the Internal Business Processes (BP) of Malaysian medium-sized firms and international factors which Gusinger (2001) termed it as Geovalent Components (GC), for its influence on OFDI Performance (OP); and determines the mediator role of Geovalent Adjustment (GA) variable on the relationship between Business Process (BP) and Geovalent Components (GC) against OFDI Performance (OP). A survey was administered for Medium-sized firms which represented by senior management of those firms, for the whole of West Malaysia. Data generated was based on 124 of those senior management's self-rating of BP, GC, GA and OP. Rasch Model and SPSS programs were employed to analyze the data using several different analyses…